Relation between 3435C > T multidrug resistance 1 gene polymorphism with high dose methylprednisolone treatment of childhood acute idiopathic thrombocytopenic purpura - Akın, Mehmet; Turgut, Sebahat; Ayada, Ceylan; Polat, Yusuf; Işık Balcı, Yasemin; Erdoğan, Fırat (Elsevier, 2011)
The current study was conducted to assess 3435C>T multidrug resistance 1 gene polymorphism and the efficacy of high dose methylprednisolone (HDMP) in childhood acute idiopathic thrombocytopenic purpura patients. Methods: A total of 31 childhood acute Idiopathic thrombocytopenic purpura patients (17 females, 14 males) between the ages of 2 and 16 years of age were included in the study. High-dose methylprednisolone was given at a dose of 30 mg/kg/day for 3 days and 20 mg/kg/day for 4 days, consecutively and intravenously. Polymerase chain reaction-restriction fragment length polymorphism was used for the detection of C3435T single nucleotide polymorphism. Fragments obtained were 238 bp to T/T genotype, 172 bp and 60 bp fragments to the C/C genotype, and 238 bp, 172 bp and 60 bp to the C/T genotype. Results: The distribution of CC, CT, and TT genotypes were 19.0%, 61.3%, and 19.4%, respectively. Both allele frequencies of C and T were the same -50%. There was no significant difference in genotype and allele distribution between the patients with LIP and the control group (chi(2)=0.84 p = 0.65, chi(2)=0.2 p = 0.63, respectively). There were no significant differences in age, gender, and pre- and post-treatment platelet counts between CC, CT, and TT genotypes of the MDR gene. Response to treatment shows no significant difference between genotype and allele groups. Conclusion: In our study, there was no difference in the HDMP treatment response between MDR1 gene genotypes. However, it should be noted that this study includes a small group of patients. Our data should therefore be considered preliminary, awaiting further confirmatory studies on an expanded patient base.
WOS: 000296823500011
PubMed ID: 21718764
Keywords: MDR1; Idiopathic Thrombocytopenic Purpura; High Dose Methylprednisolone